An optimized survey strategy for the ERIS/NIX imager: searching for young giant exoplanets and very low mass brown dwarfs using the K-peak custom photometric filter. Issue 4 (29th July 2022) - Dubber, Sophie; Biller, Beth; Bonavita, Mariangela; Allers, Katelyn; Fontanive, Clémence; Kenworthy, Matthew A; Bonnefoy, Mickaël; Taylor, William
ABSTRACT: We present optimal survey strategies for the upcoming NIX imager, part of the Enhanced Resolution Imager and Spectrograph instrument to be installed on the Very Large Telescope. We will use a custom 2.2 µm K -peak filter to optimize the efficiency of a future large-scale direct imaging survey, aiming to detect brown dwarfs and giant planets around nearby stars. We use the results of previous large-scale imaging surveys (primarily SPHERE SHINE and Gemini GPIES) to inform our choice of targets, as well as improved planet population distributions. We present four possible approaches to optimize survey target lists for the highest yield of detections: (i) targeting objects with anomalous proper motion trends, (ii) a follow-up survey of dense fields from SPHERE SHINE and Gemini GPIES, (iii) surveying nearby star-forming regions, and (iv) targeting newly discovered members of nearby young moving groups. We also compare the predicted performance of NIX to other state-of-the-art direct imaging instruments.